Advertising the accountant: a stereotype in crisis. (1st January 2014) - Miley, Frances; Read, Andrew
Although we now recognise celebrity in such diverse areas as the celebrity trainer, celebrity chef and celebrity gardener, we are yet to see the rise of the celebrity accountant. Previous research has described the accounting image as dull and boring yet recruitment advertising by the accounting profession presents a very different image. This research tries to understand that apparent inconsistency by examining the role of stereotypes in commedia dell'arte, a form of improvisational theatre that developed in 15th century Italy and which used stock characters based on the common stereotypes of the day. In this research il dottore, one of the stock characters of commedia dell'arte, is considered to show how stereotypes provide encoded information that can serve an important purpose. In addition, we contend that if the recruitment advertising by the accounting profession is successful in changing the stereotype of the accountant that has long been entrenched in popular culture, instead of being beneficial to the accounting profession, it would be deleterious. Hence, there is benefit in the accounting profession trying to maintain the stereotype.